Penerapan Teknik Cognitive Restructuring dalam Konseling Kelompok untuk mengurangi Kecemasan Belajar Siswa Kelas VIII di UPT SMPN 3 Mattirosompe (Universitas Negeri Makassar, 2021)
This study aims to determine the effectiveness of using Cognitive Restructuring Techniques in reducing learning anxiety through group counseling services. This research approach is qualitative. This type of research uses Guidance and Counseling Action Research. The group counseling service carried out includes four stages, namely the initial, transition, core and termination stages and for the Cognitive Restructuring Technique it has 6 stages which generally help students replace negative thoughts that make anxious thoughts more positive. The object of this research is 8 students of 8th grade who experience learning anxiety. The results showed that the application of Cognitive Restructuring techniques can reduce learning anxiety which is indicated by changes in student behavior and being able to think of more realistic, rational and positive statements when faced with learning conditions or situations.